An in-depth review on utilizing ultrasound biomicroscopy for assessing the iridocorneal angle and ciliary body in canines - Kim, Donghee; Kwon, Hyun; Hwang, Jiyi; Jung, Ji Seung; Park, Kyung-Mee (Frontiers in Veterinary Science, 2025)
In this review, we explore the transformative role of Ultrasound Biomicroscopy (UBM) in veterinary ophthalmology, focusing on its utility in evaluating the iridocorneal angle and ciliary body in dogs. We begin by outlining UBM’s foundational principles, providing a holistic understanding of its operational mechanics. This is followed by an exploration of the techniques and considerations for optimal UBM imaging, including the use of topical anesthesia, probe positioning, and maintaining a controlled measurement environment. A major section is dedicated to the detailed anatomy of the anterior segment, emphasizing the iridocorneal angle and ciliary body in controlling aqueous humor dynamics within canine and feline eyes. By comparing anatomical structures in humans and animals, we highlight the need for distinct parameters in veterinary medicine. The review also analyzes the parameters obtainable via UBM, emphasizing its potential in monitoring drug-induced ocular changes, gaging post-cataract surgical outcomes, and observing inter-species variations. We conclude by encapsulating the current state of research, addressing existing challenges, and suggesting future research avenues. This synthesis underscores the pivotal role of UBM in advancing veterinary ophthalmic diagnostics and research.